Ballistic Missile Defense: Capabilities and Constraints - Young, Alwyn (Tufts Archival Research Center, 2005)
Volume 8, Issue 1. Winter Numerous proposals for Ballistic Missile Defense (BMD) are receiving serious policy consideration, both in and out of government. In this article Alwyn Young examines such proposals and the advantages and disadvantages of different BMD systems in terms of the possible missions they are meant to perform. While not trying to offer judgments on the overall desirability of BMD from a strategic or arms control perspective, Young does review the current status of BMD technology and he focuses on the critical conditions that will determine BMD mission-performance capabilities.